1979
DOI: 10.1099/0022-1317-45-1-41
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Virus Antigens in Swiss Albino Mice Infected by Milk-borne Mouse Mammary Tumour Virus: the Effect of Age, Sex and Reproductive Status. II. Radioimmunoassay of Two Virus Components, gp47 and p28 in Serum and Organ Extracts

Abstract: SUMMARYExtracts of various organs, mammary tumours and sera from milk-borne MMTV infected Swiss albino mice of different age, sex and physiological conditions were tested by radioimmunoassay for the presence of gP47, the main envelope polypeptide, and p28, the main core protein of the virus. Except in brain, ovaries and testes, both antigens were found in all organs of old animals and of females after the onset of their first pregnancy. Antigens were not present in organs of weanlings or in whole foetuses. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This hypothesis also finds support in the examination of the mammary tumours. In agreement with our results, quantitative determination of p28 and gP47 by radioimmunoassay (Osterrieth et al 1979) has revealed large amounts of these antigens in the functional mammary gland, absence in the male and in the young virgin female and a highly variable expression of both antigens in mammary turnouts. No specific fluorescence was detected in organs with low antigen concentration such as the digestive tract and the epididymis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This hypothesis also finds support in the examination of the mammary tumours. In agreement with our results, quantitative determination of p28 and gP47 by radioimmunoassay (Osterrieth et al 1979) has revealed large amounts of these antigens in the functional mammary gland, absence in the male and in the young virgin female and a highly variable expression of both antigens in mammary turnouts. No specific fluorescence was detected in organs with low antigen concentration such as the digestive tract and the epididymis.…”
Section: Discussionsupporting
confidence: 78%
“…The presence of gP47 in the kidney glomeruli of MB+ Swiss mice was clearly demonstrated; only low levels of this antigen were detected by radioimmunoassay (Osterrieth et al 1979). This discrepancy might result from fluorescence pin-pointing strictly localized concentrations of antigen within the organ and/or from the participation of gP47 in immune complex deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous MMTV is present not only in the mammary glands and the prostate but also in the seminal vesicles, the vas deferens, and the epididymis, as shown by electron microscopy (274), radioimmunoassay (246), immunocytochemistry (344), and in situ hybridization (138).…”
Section: Animal Seminal Vesicles and Epididymismentioning
confidence: 99%
“…Recently, it has been shown that the production of abnormal virus particles by some lymphoma cell lines is due to a blockage of the processing of the 'env' polypeptide precursor (Nusse et al, 1979;Vaidya et al, 1980). A similar situation does not apply to the MB-mice since any gp47 reactivity cannot be detected in the mammary gland cells (Osterrieth et al, 1979). The presence of p8 (= pl0) antigen, however, has been demonstrated in the MB mammary glands by immunofluorescence , indicating that the complete precursor of the internal peptides is probably synthesized.…”
Section: Discussionmentioning
confidence: 84%
“…We have also developed an MB line by foster-nursing MB + mice on C57BL mice. The MB-Swiss mice neither produce milk viruses nor have so far presented any mammary tumours; they represent a clear example of non-coordinate virus expression since high amounts of p28 antigen are present in the mammary glands of the adult female, while the antigen gp47 cannot be detected (Osterrieth et al, 1979;Kozma et al, 1979). Such a partial expression of MMTV is also characteristically observed in the mammary glands of the GR/MTV-2-mice (Nusse et aI., 1980), and in cultures of mammary tumours and preneoplastic mammary tissues from Balb/c mice (Teramoto et al, 1980).…”
Section: Introductionmentioning
confidence: 99%